2014
DOI: 10.1371/journal.pone.0096615
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of Five Factors Relevant to In Vitro Chondrogenesis of Human Mesenchymal Stem Cells Using Factorial Design and High Throughput mRNA-Profiling

Abstract: The in vitro process of chondrogenic differentiation of mesenchymal stem cells for tissue engineering has been shown to require three-dimensional culture along with the addition of differentiation factors to the culture medium. In general, this leads to a phenotype lacking some of the cardinal features of native articular chondrocytes and their extracellular matrix. The factors used vary, but regularly include members of the transforming growth factor β superfamily and dexamethasone, sometimes in conjunction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 70 publications
0
29
0
2
Order By: Relevance
“…This design allows for accurate estimation of the effects of all individual factors and all two‐factor interactions, assuming that higher order interactions (≤4th order) are negligible. DoE methodology is extensively used in biotechnological fields for bioprocess development/optimization and is increasingly being utilized for basic and preclinical research applications, such as optimization of stem cell differentiation and antiviral drug studies . We have previously utilized FFD to screen the effects of 13 MSC‐secreted factors on the conversion of macrophages from a proinflammatory to an anti‐inflammatory phenotype .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This design allows for accurate estimation of the effects of all individual factors and all two‐factor interactions, assuming that higher order interactions (≤4th order) are negligible. DoE methodology is extensively used in biotechnological fields for bioprocess development/optimization and is increasingly being utilized for basic and preclinical research applications, such as optimization of stem cell differentiation and antiviral drug studies . We have previously utilized FFD to screen the effects of 13 MSC‐secreted factors on the conversion of macrophages from a proinflammatory to an anti‐inflammatory phenotype .…”
Section: Discussionmentioning
confidence: 99%
“…DoE methodology is extensively used in biotechnological fields for bioprocess development/optimization and is increasingly being utilized for basic and preclinical research applications, such as optimization of stem cell differentiation and antiviral drug studies. [29][30][31][32] We have previously utilized FFD to screen the effects of 13 MSC-secreted factors on the conversion of macrophages from a proinflammatory to an anti-inflammatory phenotype. 8 This study identified PGE2 as the primary MSC-secreted molecule involved in this macrophage conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative transcriptome analysis has been employed to investigate the cell response, particularly MSCs, in such 3D culture systems (Gatta et al, 2013;Hu et al, 2014;Kim et al, 2014;Pedersen et al, 2013;Roobrouck et al, 2011;Wu et al, 2012;Han et al, 2013; A C C E P T E D M A N U S C R I P T Jakobsen et al, 2014;Neuss et al, 2011). For example, a study by Han et on the scaffolds made with poly(lactic acid) than those made with poly(ɛ-caprolactone) (Neuss et al, 2011).…”
Section: Optimizing Culture Conditionsmentioning
confidence: 99%
“…However, this also induced undesirable molecules, thus, indicating a need for improvement in the differentiation protocols (Jakobsen et al, 2014).…”
Section: Optimizing Culture Conditionsmentioning
confidence: 99%
“…Corticosteroids are one such bioactive substance. When acting alone, corticosteroids may facilitate tissue atrophy and joint destruction; however, when acting in synergy with other factors, they have been demonstrated to increase a number of chondrogenic markers (10), in addition to aiding in the accumulation of extracellular matrix, which is necessary for the formation of cartilage (11). In addition, substances that contain insulin or certain organic acids favor chondrogenesis (1214).…”
Section: Introductionmentioning
confidence: 99%